AGAR MEDIUM FOR HUMAN UREAPLASMA UREALYTICUM - Raddi, MSG; Lorencetti, N. C.; Rossini, A. J. (Soc Brasileira Microbiologia, 1992)
The authors wish to report a simple medium for the isolation and cultivation of Ureaplasma urealyticum starting from clinical materials. This medium induced growth in eleven of the twelve different serotypes of Ureaplasma urealyticum studied.
Keywords: UREAPLASMA-UREALYTICUM; UREAPLASMA CULTURE MEDIUM